IMPLEMENTASI KEBIJAKAN PROGRAM PEMBANGUNAN INFRASTRUKTUR PEDESAAN (PPIP) DI DESA LOPANA SATU KECAMATAN AMURANG TIMUR KABUPATEN MINAHASA SELATAN - Ismail Nurdin; Megawati Cindy Rorimpandey (Institut Pemerintahan Dalam Negeri, 2019)
The purpose of this study is to describe comprehensively and provide recommendations from the results of this PPIP research program. This study uses the theory of Edward III. This research is a qualitative research using descriptive methods through a deductive approach. The technique of collecting data is done by interviews, observation, and documentation. Based on the results of the study, it is known that the PPIP Program Implementation in Lopana Satu Village has not run optimally. This causes the Village Development to proceed slowly. Then the community has distrust in the implementation of the program due to the failure of development in the previous program period. This program also has problems in managing funds that are a resource in this program. For this reason, the Regional Government should pay more attention to matters, namely approaching the community for the smooth running of the program and improving management problems and the PPIP funding budget Keywords: Policy Implementation, Rural Infrastructure Development Program, and Adequate Infrastructure